Rapid and high biodegradation of phenols catalyzed by Candida tropicalis NCIM 3556 cells - Varma, Rita J.; Gaikwad, Bhaskar G. (Enzyme and Microbial Technology, 2008)
Cells of 19 yeast cultures, belonging to genus Candida were screened for biodegradation of phenol. The cultures procured from NCIM culture collection and were selected so as to contain a representative of varied strains of the species. These were grown in MGYP3 medium and tested for biodegradation of phenol. C. tropicalis (CT) nos. 3118, 3556 and C. lipolytica 3472 effectively degraded >90% 2 g l(-1) phenol. The C. tropicalis 3556 strain was selected for further studies as it metabolized >95% phenol in just 16 h as compared to the other two which took 48 h. The maximum substrate concentration that could be completely degraded was 2 g l(-1). A study of induction, of different concentration of phenol in the growth medium showed that toxicity to cell growth increased with increasing phenol levels in growth media. Biodegradation of phenol derivatives - o-cresol, m-cresol. 2,6-dimethyl phenol, alpha-naphthol, o-chlorophenol and p-nitrophenol, by the selected three strains indicated that the specificity of each culture varied for different substrate. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Biodegradation; Candida lipolytica; Candida tropicalis; phenol; Phenol derivatives